Individual Dispositions and Situational Stressors in Competitive Sport: The Role of Stress Mindset in the Cognitive Appraisals Processes - Čopec, Dajana; Karlović Vragolov, Matea; Buško, Vesna (Frontiers in Psychology, 2022)
Personality has widely been documented to play an important role in the cognitive appraisal and stress processes. Emerging research highlight the stress mindset as a new concept that could add to understanding of individual differences in stress experiences. This study aimed to examine the relative contribution of Big Five personality dimensions and stress mindset in accounting for measures of cognitive appraisals of stress among the competing athletes. The study was conducted on the sample of 125 collegiate athletes of both gender who actively compete in sport. All the participants were regular undergraduate or graduate students at the Faculty of Kinesiology of the University of Zagreb. A questionnaire including demographic information about athletes and their sport career, Stress Mindset Measure (SMM), situation specific Cognitive appraisal scale, Sources of Stress scale, and personality scale measured by IPIP-50, was administered in an online form using the Google Forms platform. Multivariate hierarchical regression procedures resulted in somewhat different predictor structures accounting for cognitive appraisals of threat, loss, and challenge, used as criterion variables. The set of Big Five personality dimensions as well as stress mindset measure proved to have significant additive contribution to the explanation of each of three cognitive appraisal criterion variance. The study results support the current body of literature suggesting a unique role of the stress mindset construct in explaining individual differences in cognitive stress appraisal among athletes above and beyond general personality dimensions.